Construction of a management protocol for high-risk neurogenic bladder in Chinese patients with type 2 diabetes: a Delphi study - Luo, Senying; Ren, Wei; Hu, YingJie; Deng, Ting; Lai, Wenjuan; Cai, Wenzhi (Frontiers in Endocrinology, 2025)
ObjectivesThe objective of this study is to establish an evidence-based protocol for managing high-risk neurogenic bladder (NB) in Chinese patients with T2DM, integrating risk stratification to standardize clinical practice in China region.MethodsThrough a two-round Delphi consensus process involving 20 national experts and evidence synthesis from 13 clinical guidelines and a systematic review, we developed China’s first hierarchical NB risk stratification system. Quantitative analyses incorporated authority weighting (0–1 scale), coordination coefficients, and Kendall’s concordance testing across 81 systematically validated clinical indicators.ResultsHigh expert engagement persisted through both rounds (Round 1: 90% response rate; Round 2: 94.7%). Consensus levels demonstrated progressive improvement, with primary indicators achieving the most substantial enhancement (Kendall’s W: 0.289 vs. 0.391, 35.3% improvement). Secondary and tertiary indicators showed 5.5% and 27.4% increases respectively (all p<0.01). The final protocol reached a consensus, including 4 primary indicators, 17 secondary indicators, and 60 tertiary indicators.ConclusionThis consensus-driven framework provides innovative clinical tools for NB risk stratification in diabetes care. Its three-tiered structure—integrating policy recommendations, clinical algorithms, and bedside assessment protocols—significantly improves patient management and outcomes, serving as a valuable resource to guide clinical practice.